Use of an Under-Water Compressed Air Energy Storage (UWCAES) to Fully Power the Sicily Region (Italy) With Renewable Energy: A Case Study - Tiano, Francesco Antonio; Rizzo, Gianfranco (Frontiers in Mechanical Engineering, 2021)
A case study for fully power the Sicily region (Italy) with renewable energy source (wind and photovoltaic) is presented. To overcome the problem of non-programmability of renewable sources, an energy storage system consisting of under water compressed air energy storage (UWCAES) is used. From the real annual capacity values of the renewable plants installed in Sicily, a sizing of both the energy production and the storage system and its auxiliary services is evaluated. The optimization of the operation of the system as a whole, modeled with mathematical models already validated in previous studies, is obtained through dynamic programming. The results show that carbon-free feeding is possible and that all the boundary conditions on the operation of the system are met.